Estimation of Three-Dimensional Solubility Parameters of DM-700 Polyester Resin by Turbidity Titration. (November 2019) - Liu, Qiang; Shi, Xiaoqin; Lu, Yanqiu; Dong, Liming
Abstract: According to the method of turbidity titration and 63 cloud point data minimum volume closure ellipsoid fitting, the solubility parameter of polyester resin DM-700 was determined to be 22.84(MPa) 1/2, and the three-dimensional solubility parameter was (δd =17.15 (MPa) 1/2 ; δp =9.97(MPa) 1/2 ; δH =11.32(MPa) 1/2 ). This value is close to the result calculated by the group contribution method (22.68(MPa) 1/2 ), which further proves that the method is accurate and reliable.